PENDIDIKAN KARAKTER DI PESANTREN (Studi Kasus di Pesantren Nur Ilahi-Sui Kinjil-Benua Kayong- Ketapang Kalimantan Barat) - Jenuri, Jenuri (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Education system in Islamic boarding school successfully produce religious figures, zuama’ (influencing leaders), even politicians, and until today many national leaders now had studied in Islamic boarding school as well. Characterization process of the values that made Islamic Boarding School Nur Ilahi in grounding the character education include: honesty, responsibility and compliance, speech/preaching, intelligence, independence, leadership, discipline, providing penalties, prize giving, the way in dressing, simplicity, cleanliness, mutual aid, generosity, and tolerance. Key Words: Islamic Boarding School, Character, and Education.